DEVELOPMENT OF TEACHING MATERIALS "QUANTITATIVE RESEARCH METHODOLOGY FOR STUDENTS BASED ON QR CODE - Etin Solihatin; Roby Ibnu Syarifain; Jhoni Lagun Siang; Raharjo; Moch. Sukardjo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The problem in research that you want to find a solution to is 1) How is the development of "Quantitative Research Methodology" teaching materials for students based on QR Code? 2) how is the effectiveness of "Quantitative Research Methodology" teaching materials for students based on QR Code? The operational objective is to improve quantitative research proposals. The research method used is Research and Development with the Dick and Carey’s model. The results showed that the average learning score of the research methodology, after using QR Code-based research methodology teaching materials, was higher than the learning outcomes before using QR Code-based quantitative research methodology teaching materials. 7 = 8.41> 7.03. Based on the t-test calculation, it is obtained tcount = (11.67)> t table (2.05). Which means a significant increase in learning outcomes Research Methodology using QR Code-based Quantitative Research Methodology teaching materials. A combination of text and QR Code leads to better learning than just text. Which means that the results of learning Research Methodology will be better if QR Code-based Quantitative Research Methodology teaching materials are used, when compared to reading the material alone.